Studying the Uptake of Toxic Metals by Plants using New Mathematical Modeling - Hussein Hassan Kharnoob; Hasan Ahmed Hasan (Tikrit Journal of Pure Science, 2023)
Two plants species were used to study the uptake of heavy metals by plants; these were Lolium perenne and Cock's Foot. The species were grown in Hoagland's solution with double concentration of phosphate for one week; the roots species were cut and grown in Hoagland's solution without phosphate to prevent precipitation of any metal phosphate. Four experiments were run with a composite rotatable design with three variables and at five levels (-1.68,-1,o,+1,+1.68) was used. The metals were added as metal nitrate to Hoagland's solution in which the plants are grown on a logarithmic scale and after one week of grown the roots and shoots of plant were cut and digested with concentrated nitric acid and examined for metals by atomic absorption spectrophotometer. This research proved that some elements increased the absorption of other elements in growth solution to the shoot through root while other elements interfere the absorption phenomena for example zinc effects on absorption of copper